Chronic and Binge Alcohol Ingestion Increases Truncated Oxidized Phosphatidylcholines in Mice Lungs Due to Increased Oxidative Stress - Appolonia, Corynn N.; Wolf, Kaelin M.; Zawatsky, Charles N.; Cinar, Resat (Frontiers in Physiology, 2022)
Heavy alcohol drinking has negative health effects in multiple organs. It predisposes lungs to inflammatory conditions associated with acute lung injury and increased incidence of pneumonia and sepsis, which may lead to death due to acute respiratory distress syndrome in some individuals with alcohol use disorder (AUD). In general, rodent models of alcohol exposure either do not recapitulate multiple organ injuries as seen in humans or require longer duration to establish tissue injury and inflammation. The recently introduced NIAAA model of alcohol-induced liver injury, characterized by a marked increase in steatosis and liver damage with 10 days of a liquid diet containing 5% ethanol followed by a single ethanol binge (5 g/kg). Therefore, we employed this model to explore the status of surfactant phospholipids, oxidative stress, tissue injury markers and inflammatory cytokines in lungs. In lungs of C57BL/6J mice, the alcohol feeding significantly increased levels of the surfactant phospholipid dipalmitoyl phosphatidylcholine (DPPC) as well as the truncated oxidized phosphatidylcholines palmitoyl oxovaleryl phosphatidyl-choline (POVPC), palmitoyl glutaryl phosphatidyl-choline (PGPC), palmitoyl oxo-nonanoyl phosphatidyl-choline (ALDO-PC), and palmitoyl azelaoyl phosphatidyl-choline (PAzePC) at 9 hours post-binge. Additionally, gene expression of the enzymes catalyzing lipid oxidation, such as arachidonate 15-lipoxygenase (Alox15), prostaglandin synthase 2 (Ptgs2), Cytochrome P450 2E1 (Cyp2E1) and NADPH oxidase 1 (Nox1) were significantly increased. Furthermore, ethanol increased levels of the inflammatory cytokine Interleukin-17 in bronchoalveolar lavage fluid. In conclusion, the NIAAA alcohol feeding model might be suitable to study alcohol-induced lung injury and inflammation.